The resilience of youth delinquent. Education as a protective factor - Ungureanu, Roxana; Tomita, Mihaela (Technium Social Sciences Journal, 2021)
Adolescents face difficult developmental tasks and multiple challenges and are exposed to very varied risk factors. In case the protection factors are not strong enough, they can generate many difficulties or emotional and behavioral disorders, especially due to the fragility and vulnerability of the adolescent’s inner world during this period. This paper presents an analysis of the protection factors underlying the resilience of young offenders admitted in educational centers in Romania. The analysis is part of a broader research conducted in a doctoral thesis. The conclusions show us that the basic pillar of reeducating these young people relies in completing their studies at least at the level of primary school and the orientation towards learning a profession, so that those who blame material deprivation as the cause of delinquency have the possibility to earn a living through work.